PERCEPTIONS OF DARKNESS: MOBILE MEDIA AND THE EMBODIMENT OF RISK AND SAFETY IN THE URBAN NIGHT - Hardley, Jess; Richardson, Ingrid (AoIR Selected Papers of Internet Research, 2019)
This paper explores the embodied experience of smartphone users in urban darkness, and considers how the geo-locative and network functionality of mobile media impacts upon the perception of safety and risk at night. City spaces at nighttime are often perceived as less safe, and the habitual trust we place in familiar strangers during the day can become imbued with caution, suspicion and fear. Much of the research in this area neglects the impact of both the networked infrastructure of the city – what de Souza e Silva and Sutko (2009) term “net-local space” – and the place of mobile media in people’s nighttime practices and their experience and perception of the urban dark. This paper draws on original ethnographic data collected in Perth and Melbourne from 2015-2017 to examine how mobile devices as both communicative and location-aware interfaces are used to provide women with a perceived or ‘felt’ sense of bodily safety and security, and the potential implications this has on users’ pedestrian traversal of the urban dark. Throughout the paper, our conceptual and ethnographic approach is informed by Merleau-Ponty’s (1945) work on habituation and proprioception, Ihde’s (1993) postphenomenological take on the cultural specificity of the body-technology relation, and Weiss’s (1999) feminist adaptation of the term intercorporeality. The theme of “trust” runs as a thread through this paper, as we unpack the mistrust city dwellers have of the urban dark and how mobile media perceptually ameliorates this embodied sense of risk by extending users communicative reach via location-aware interfaces.